Draft Annual Plan 1986-87 Volume VIII Transport and Communication Jammu and Kashmir Government - Planning Commission (Planning Commission, 1985)
The J&K State Comprises mostly of Hilly terrain where the main source of communication is through the net work of roads. A well and efficient road system is a pre-requisite not only for communication facilities but also a vital factor contributing to the overall Development of the State including agriculture and Animal Husbandry. For exploitation of Mineral forest, Industrial and water resources which the nature has generously bestowed upon the state, it is all the more necessary to explore new horizon's for the expansion of this road system and upgrading/improving the existing ones to provide-more and more access to the land locked and un-explored pockets/areas.
Jammu and Kashmir Government, Planning and Development Department